2021
DOI: 10.21273/hortsci15818-21
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cognitive Function and Emotional Condition Measured Using Electroencephalography in the Elderly during Horticultural Activities

Abstract: The aim of this study was to compare the physiological and psychological effects in the elderly during horticultural and nonhorticultural activities as leisure activities. A total of 58 participants aged 65 or older (29 men and 29 women; average age, 74.0 ± 4.7) whose cognitive function was within the normal range were included in this study. Participants performed four horticultural and four nonhorticultural activities for 2 min, respectively. The study had a cross-over experimental design. Electroencephalogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 62 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…The result of the horticultural activity program for the elderly with mild to moderate dementia was that the Vitality Index and Mini-Mental State Examination scores improved significantly after the horticultural activity program was implemented compared with before the program [70]. In a similar study, horticultural activities such as seed sowing and plant planting had a positive effect on cognitive function and emotional stability by activating the brains of elderly participants compared with general leisure activities [55].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The result of the horticultural activity program for the elderly with mild to moderate dementia was that the Vitality Index and Mini-Mental State Examination scores improved significantly after the horticultural activity program was implemented compared with before the program [70]. In a similar study, horticultural activities such as seed sowing and plant planting had a positive effect on cognitive function and emotional stability by activating the brains of elderly participants compared with general leisure activities [55].…”
Section: Discussionmentioning
confidence: 91%
“…Beta waves are subdivided into RLB (12-15 Hz), relative mid beta (15)(16)(17)(18)(19)(20), and relative high beta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and when activated, they improve concentration and attention [53,54]. According to previous studies, an increase in beta bands is associated with improvements in cognitive functions such as memory function, language function, and attention [55]. An increase in the beta bands may help improve or maintain cognitive function [46].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that FA can promote people’s physical and mental health. Seon-Ok Kim showed that the total mood disorder score of elderly was lowered after FA, indicating a positive effect on the mood of participants [ 50 ]. FA can effectively reduce the total emotional disorder and anxiety of the Psychology teacher [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four activities were then performed in random order: connecting the components, planting, coding, and the combined coding and horticultural task. Each activity was performed for 5 min by referring to an electroencephalograph (EEG) measurement study on horticultural activities and considering the time needed to complete the activity (Oh et al, 2019;Kim et al, 2021aKim et al, , 2021b. In addition, participants were requested to avoid speaking or moving more than necessary because such movements may influence the brain-wave measurements.…”
Section: Methodsmentioning
confidence: 99%
“…4A). This device minimized the risk of electric shock compared with wet electrode systems that use an electrolyte gel (Kim et al, 2021b). In addition, it has the advantage of quicker setup time, increased versatility, and improved mobility (Okolo and Omurtag, 2018).…”
Section: Methodsmentioning
confidence: 99%